Combustion Calorimetric Studies on Urea-Carboxylic Acid Inclusion Complexes - Ahmad, Jamil; Selei, Seadimo (Asian Journal of Chemistry, 2016)
Inclusion complexes of urea with several long-chain fatty acids (containing 10 to 22 C atoms) were prepared and their heats of combustion were measured using an isoperibol bomb calorimeter. The internal energy of combustion increases approximately linearly with the number of C atoms in the fatty acid used to make the complex.